ANALISIS COST VOLUME PROFIT (CVP) UNTUK PERENCANAAN LABA PADA SELABINTANA HOTEL & CONFERENCE RESORT - Syabrina, Syabrina; Nugroho, Gatot Wahyu (COMPETITIVE, 2023)
The hotel industry is currently experiencing a decline in profits due to government policies regarding the COVID-19 pandemic, in addition to classic problems such as rising costs every year and the increasing number of competitors affecting profit. to make a good profit planning managers need to understand the relationship between costs, sales volume and profit by using cost volume profit analysis. The method used is descriptive qualitative with triangulation data collection techniques. The results show that Selabintana Hotel & Conference Resort does not use cost volume profit analysis for its profit planning, profit declines from 2018 and losses in 2020. According to the results of cost volume profit analysis, the company needs to achieve sales at the break-even point first for the following year. , by reducing costs, finding cheaper raw materials, saving inventory, and limiting purchases. Increasing sales volume can carry out promotions and innovations that do not cost a lot, so that sales revenue is not absorbed much into cost.